A PGSE NMR approach to the characterization of single and multi-site halogen-bonded adducts in solution. Issue 84 (26th August 2016) - Ciancaleoni, Gianluca; Macchioni, Alceo; Rocchigiani, Luca; Zuccaccia, Cristiano
Abstract : The diffusional PGSE NMR technique allows a detailed characterization of single- and multi-site halogen-bonded systems. Abstract : We demonstrate here that the Pulsed field Gradient Spin Echo (PGSE) NMR diffusion technique can be effectively used as a complementary tool for the characterization of mono- and multi-site intermolecular halogen bonding (XB) in solution. The main advantage of this technique is that it provides the possibility of unambiguously determining the stoichiometry of the supramolecular adduct, information that is particularly important when multi-site molecular systems are studied. As an example, PGSE NMR measurements in chloroform indicate that hexamethylenetetramine (HMTA ), a potentially four-site XB acceptor, actually exploits only two sites for the interaction with the XB donor N -bromosuccinimide (NBS ), leaving the other two nitrogen sites unoccupied. Charge displacement calculations suggest that this is due also to the anti-cooperativity of the XB interaction betweenHMTA andNBS .